Die Ordnung der Inszenierung - Wilharm, Heiner (transcript, 2015)
The scene is omnipresent. It originated in the theater, but we know and experience it as the political, public, private, profane, and sacred scene as well. Away from the stages of art, media, and entertainment, staging takes place.In a historically and systematically sweeping »extended scenography« that integrates design and compositional thought and sees itself as practical knowledge, Heiner Wilharm surveys the variations of scenic resolution of design and composition intentions in everyday actions and experience, such as in literature and science. Scenic resolution, according to the author, is carried out according to the practical and even theoretical use of sign and meaning, as an act and performance or additionally, as a presentation and representation. The thus-emerging theory of action and meaning, until now associated with the philosophy of Charles S. Peirce, undertakes a comprehensive assessment of the scenic and the staged both within and beyond the arts.